Descriptive study of severe hospitalized cases of laboratory-confirmed influenza during five epidemic seasons (2010–2015) - Núria Torner; Ana Martínez; Luca Basile; MMar Mosquera; Andrés Antón; Cristina Rius; M. Rosa Sala; Sofia Minguell; Elsa Plasencia; Mónica Carol; Pere Godoy; Núria Follia; et al. (BMC Research Notes, 2018)
Abstract Objective The Plan of Information on Acute Respiratory Infections in Catalonia (PIDIRAC) included the surveillance of severe hospitalized cases of laboratory-confirmed influenza (SHCLCI) in 2009. The objective of this study was to determine the clinical, epidemiological and virological features of SHCLCI recorded in 12 sentinel hospitals during five influenza seasons. Results From a sample of SHCLCI recorded during the 5 influenza epidemics seasons from 2010–2011 to 2014–2015, Cases were confirmed by PCR and/or viral isolation in cell cultures from respiratory samples. A total of 1400 SHCLCI were recorded, 33% required ICU admission and 12% died. The median age of cases was 61 years (range 0–101 years); 70.5% were unvaccinated; 80.4% received antiviral treatment (in 79.6 and 24% of cases within 48 h after hospital admission and the onset of symptoms, respectively); influenza virus A [37.9% A (H1N1)pdm09, 29.3% A (H3N2)] was identified in 87.7% of cases. Surveillance of SHCLCI provides an estimate of the severity of seasonal influenza epidemics and the identification and characterization of at-risk groups in order to facilitate preventive measures such as vaccination and early antiviral treatment.